The effect of the presence of an audience on risk-taking while gambling: the social shield. (3rd July 2017) - Lemoine, Jérémy E.; Roland-Lévy, Christine
Abstract: Being in a social context influences risk-taking behavior. This study aims to identify the effect of an audience's presence on risk-taking while gambling. One hundred and thirty-two university students played a computer roulette game. They were randomly allocated to one of our three conditions: (i) either they played alone; or (ii) in the presence of the experimenter; or (iii) in the presence of the experimenter, while being videotaped. Results revealed a significant effect on risk-taking in the participants with the presence of an audience, with more risk-averse behaviors in the two types of audience conditions than in the alone condition. No differences were found between the two audience conditions. Thus, an audience may prevent risk-taking and provide a social shield.